TechQuity is an imperative for health and technology business: Let's work together to achieve it. (22nd June 2021) - Clark, Cheryl R; Akdas, Yasemin; Wilkins, Consuelo H; Rhee, Kyu; Johnson, Kevin B; Bates, David W; Dankwa-Mullan, Irene
Abstract: Open discussions of social justice and health inequities may be an uncommon focus within information technology science, business, and health care delivery partnerships. However, the COVID-19 pandemic—which disproportionately affected Black, indigenous, and people of color—has reinforced the need to examine and define roles that technology partners should play to lead anti-racism efforts through our work. In our perspective piece, we describe the imperative to prioritize TechQuity —equity and social justice as a technology business strategy—through collaborating in partnerships that focus on eliminating racial and social inequities.